Pengaruh Self Confidence terhadap Kemampuan Komunikasi Matematis Siswa Kelas VIII MTsN 1 Mataram Tahun Ajaran 2025/2026 - Zavira Mardhatillah; Ketut Sarjana; Eka Kurniawan (Griya Journal of Mathematics Education and Application, 2026)
This study aims to determine the significant effect of self-confidence on the mathematical communication skills of eighth-grade students at MTsN 1 Mataram in the 2025/2026 academic year. This study used a quantitative method with an ex post facto approach. The population in this study was all 406 eighth-grade students, with a sample of 108 students selected using cluster random sampling. Data collection techniques in this study used a self-confidence questionnaire and a mathematical communication skills test. Data analysis techniques used were descriptive and inferential statistical analysis with the help of SPSS. The results of the data analysis obtained a regression equation of , a correlation coefficient of 0.721, and a coefficient of determination of 52%. This indicates a significant effect of self-confidence on students' mathematical communication skills.